Ethical Values and Environmentalism in China: Comparing Employees from State-Owned and Private Firms - Chun, Rosa (Journal of business ethics, 2009)
Industrial pollution is of both national and international concern in the context where one country’s emissions contribute to the problem of global warming. Existing studies have focused on government and regulations rather than on employees. The context of this study is in respect of 472 workers in seven Chinese energy companies in Shanxi province in China, one of the biggest coal mining regions and a region most responsible for environmental pollution. The key findings are two-fold: first, employees’ values were positively correlated with attitudes toward the environment, which also correlates with perceived corporate citizenship; second, the ownership type of the firm had a significant influence on corporate citizenship, employee values and their attitudes toward environment. Contrary to existing beliefs, State-owned enterprises in China have much poorer ratings on all the three constructs compared to privately owned companies. The results highlight the role of the government and policy makers in shaping employees’ attitudes toward the environment, and in turn the corporate citizenship of the Chinese energy industry.